Inhibition of Ctsk alleviates periodontitis and comorbid rheumatoid arthritis via downregulation of the TLR9 signalling pathway. (10th March 2019) - Pan, Weiyi; Yin, Wuwei; Yang, Li; Xue, Lili; Ren, Jie; Wei, Wei; Lu, Qiuyu; Ding, Handong; Liu, Zhaohui; Nabar, Neel R.; Wang, Min; Hao, Liang
Abstract: Aim: In this study, we investigate the mechanistic link between rheumatoid arthritis (RA) and periodontitis to identify a novel target (cathepsin K; Ctsk) for the treatment of comorbid periodontitis and RA. Methods: An experimental model of periodontitis with arthritis was established in DBA/1 mice. We then tested the effect of BML‐244, a specific inhibitor of Ctsk, by quantifying several inflammatory markers of TLR9 signalling both in vivo and in vitro. Results: Our results showed that periodontitis–rheumatoid arthritis comorbidity causes severer periodontal bone and joint cartilage destruction than either disease alone. Inhibition of Ctsk reduced infiltration by dendritic cells and T cells and inflammatory cytokine production; these improvements alleviated the hard‐tissue erosion in periodontitis and RA as measured by bone erosion in periodontal lesions and cartilage destruction in knee joints. Inhibition of Ctsk also decreased the expression of TLR4 and TLR9 in vivo, whereas in vitro experiments indicated that Ctsk is involved specifically in the production of cytokines in response to TLR9 engagement. Conclusion: Our data reveal that periodontitis and RA may have additive pathological effects through dysregulation of the TLR9 pathway and that Ctsk is a critical mediator of this pathway and contributes to the pathogenesis of RA and periodontitis.